S01-2: Older People on the Move Programme Offers New Opportunities for Sports Clubs to Promote Physical Activity in Older Adults (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: As the population ages, older adults are living longer, staying active, and increasingly seeking diverse opportunities for physical activity. This demographic change presents both challenges and opportunities: meaningful and accessible exercise options are needed for this growing group. Sports clubs offer a promising platform, but in Finland, they have so far provided limited services for older adults. Many clubs also lack the necessary knowledge and skills to initiate age-inclusive activities.Project or Policy Description: Development. The Age Institute coordinates a national Older People on the Move Programme (OPMP), which promotes active lifestyle among older adults. As part of this work, OPMP has organised educational events for 157 sports clubs, which have expressed a clear need for support in adapting their activities for older adults. Currently, no ready-made concepts for this purpose exist in Finland.To address this need, OPMP, in collaboration with the Finnish Gymnastics Federation, has designed and conceptualised adapted artistic gymnastics for older adults. This activity consists mainly of multi-component physical exercises, which are an essential part of the physical activity guidelines for older adults.Implementation: The concept, which was piloted with older adults, includes a guide with three difficulty levels, instructional videos, and instructor training. Training is organised in cooperation with the Gymnastics Federation: The Federation provides content on adapted artistic gymnastics, while OPMP covers age-specific exercise principles. Implementation was started in 2024 and training is scheduled for a broader dissemination.Evaluation: OPMP piloted the concept and its instructor training with 13 gymnastics clubs. The training was evaluated useful (mean rating points 4.4/5) and would be recommended to others (mean 9.8/10).Dissemination: After completing the training, participants implement the activities locally. The guide and videos are freely available, and regular training sessions are scheduled to support further dissemination.Conclusions: Sports clubs need support in organising physical activities for older adults. This concept of adapted artistic gymnastics provides an effective, scalable solution. Conceptualisation can also be adapted to other sports.Keywords: Active ageing, adapted sports, sports clubs